Cortical and subcortical distribution of middle and long latency auditory and visual evoked potentials in a cognitive (CNV) paradigm - Bares, Martin; Rektor, Ivan; Kanovský, Petr; Streitová, Hana (Clinical neurophysiology, 2003)
OBJECTIVE: This study concerned sensory processing (post-stimulus late evoked potential components) in different parts of the human brain as related to a motor task (hand movement) in a cognitive paradigm (Contingent Negative Variation). The focus of the study was on the time and space distribution of middle and late post-stimulus evoked potential (EP) components, and on the processing of sensory information in the subcortical-cortical networks. METHODS: Stereoelectroencephalography (SEEG) recordings of the contingent negative variation (CNV) in an audio-visual paradigm with a motor task were taken from 30 patients (27 patients with drug-resistant epilepsy; 3 patients with chronic thalamic pain). The intracerebral recordings were taken from 337 cortical sites (primary sensorimotor area (SM1); supplementary motor area (SMA); the cingulate gyrus; the orbitofrontal, premotor and dorsolateral prefrontal cortices; the temporal cortex, including the amygdalohippocampal complex; the parietooccipital lobes; and the insula) and from subcortical structures (the basal ganglia and the posterior thalamus). The concurrent scalp recordings were obtained from 3 patients in the thalamic group. In 4 patients in the epilepsy group, scalp recordings were taken separately from the SEEG procedure. The middle and long latency evoked potentials following an auditory warning (S1) and a visual imperative (S2) stimuli were analyzed. The occurrences of EPs were studied in two time windows (200-300 ms; and over 300 ms) following S1 and S2. RESULTS: Following S1, a high frequency of EP with latencies over 200 ms was observed in the primary sensorimotor area, the supplementary motor area, the premotor cortex, the orbitofrontal cortex, the cingulate gyrus, some parts of the temporal lobe, the basal ganglia, the insula, and the posterior thalamus. Following S2, a high frequency of EP in both of the time windows over 200 ms was observed in the SM1, the SMA, the premotor and dorsolateral prefrontal cortex, the orbitofrontal cortex, the cingulate gyrus, the basal ganglia, the posterior thalamus, and in some parts of the temporal cortex. The concurrent scalp recordings in the thalamic group of patients twice revealed potentials peaking approximately at 215 ms following S1. Following S2, EP occurred with latencies of 215 and 310 ms, respectively. Following S1, separate scalp recordings in 4 patients in the epilepsy group displayed EP 3 times in the 'over 300 ms' time window. Following S2, EP were presented once in the '200-300 ms' time window and 3 times in the 'over 300 ms' time window. CONCLUSIONS: The SM1, the SMA, multiple sites of the frontal lobe, some parts of the temporal lobe, the cingulate gyrus, the basal ganglia, the insula, and the posterior thalamus all participate in a cortico-subcortical network that is important for the parallel cognitive processing of sensory information in a movement related task.
Keywords: dospělí; Thalamus; Epilepsies, Partial; reakční čas; thalamus; Humans; Reaction Time; lidé středního věku; sluchové evokované potenciály; Middle Aged; elektroencefalografie; Motor Activity; zrakové evokované potenciály; Cerebral Cortex; pohybová aktivita; mužské pohlaví; epilepsie parciální; kontingentní negativní variace; Adult; Basal Ganglia; Adolescent; mozková kůra; Electroencephalography; ženské pohlaví; bolest; Female; Scalp; Evoked Potentials, Visual; lidé; Evoked Potentials, Auditory; mladiství; Contingent Negative Variation; Male; bazální ganglia; Pain; skalp